Analisis Keterlaksanaan Kompetensi Psikomotorik (KD.4) pada Pembelajaran Biologi Kelas XI SMA di Kota Makassar pada Masa Pandemi Covid-19 - Nurinayah Nurinayah; Andi Asmawati Azis; Abdul Muis (Biology Teaching and Learning, 2022)
Abstract. This study aims to determine the indicators of the basic competencies developed by teachers have reached the curriculum standard and to determine the psychomotor competence (KD.4) in biology learning in class XI SMA developed by teachers during the pandemic. This research is quantitative descriptive. The research instrument used in this study used a questionnaire instrument that was distributed to 11th grade high school students and XI high school biology teachers. This instrument uses the Guttman scale which has been through expert validation by 2 expert lecturers. The research subjects were 5 teachers and 319 students from 3 different schools, namely SMAN 9 Makassar, SMAN11 Makassar and SMAS Bosowa School Makassar. Techniques Data collection was carried out with students and teachers each filling out a questionnaire that had been made in the form of online forms, documentation and interviews, the collected data were analyzed using descriptive statistical analysis techniques. The results showed that there were only 3 biology teachers who developed indicators for achieving curriculum standards and 2 other teachers did not achieve curriculum standards, namely SMAN 9 Makassar and SMAS Bosowa School Makassar. Not all indicators developed by teachers are implemented, the average percentage of implementation is in the range of 40% ≤X ≤60% which can be categorized as quite implemented.Keywords: psychomotor, pandemic, curriculum, high school.